1999
DOI: 10.5380/cep.v17i2.13780
|View full text |Cite
|
Sign up to set email alerts
|

Conservação Pós-Colheita Do Maracujá Doce Com Ceras Comerciais

Abstract: Verificou-se o efeito do uso de ceras comerciais em maracujá doce (Passiflora alata Dryander). Após a desinfecção dos frutos com thiabendazol (0,5 g/L), estes foram secos à sombra, e imersos por 1 minuto, em diferentes tipos de ceras comerciais, todas na diluição 1:1 (constituindo os tratamentos: 1) Testemunha; 2) Cera Sta-fresh; 3) Cera Fruit wax; 4) Cera Sparcitrus; e 5) Cera Citrosol). Os frutos foram avaliados semanalmente quanto à perda de peso, textura, rendimento de suco, sólidos solúveis totais, acidez… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
4
1

Year Published

2017
2017
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 2 publications
3
4
1
Order By: Relevance
“…The storage conditions and the use of packaging and wax provided significant changes in the physiological variables, which directly influenced the post-harvest shelf life of P. alata fruits. The same occurred in the reports of Junqueira et al (2003) and Silva et al (1999).…”
Section: Resultssupporting
confidence: 81%
See 2 more Smart Citations
“…The storage conditions and the use of packaging and wax provided significant changes in the physiological variables, which directly influenced the post-harvest shelf life of P. alata fruits. The same occurred in the reports of Junqueira et al (2003) and Silva et al (1999).…”
Section: Resultssupporting
confidence: 81%
“…Blum et al (2008) reported that immersion of persimmon fruits (Diospyrus kaki) in a solution with 12.5% carnauba wax was efficient in maintaining ascorbic acid levels and tissue firmness, allowing storage for up to 49 days. Silva et al (1999) found that fruits of P. alata immersed in carnauba wax, and maintained at a temperature of 9 °C and relative humidity between 85% and 90%, also had lower loss of fresh mass and less wilting when compared to the untreated control. Junqueira et al (2003), reported that fruits of P. alata stored in refrigerated environment (5 °C and 90% RH) had lower fresh mass loss and lower incidence of anthracnose, the most common post-harvest fungal disease on P. alata, when compared to fruits kept at room temperature (23 °C and 65% RH).…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…The alcohols 1-hexanol and 2-heptanol, which are among impact compounds in commercial passion fruits aroma [22,25,38], were identified in the present study (Table 1) and may be important for sweet passion fruit aroma.…”
Section: Other Classes Of Volatile Compoundsmentioning
confidence: 95%
“…Aldehydes and organic acids have been identified in other passion fruit species [4,11,22,28], but not in the sweet passion fruit, except for very low concentrations of acetic acid (possibly derived from pulp fermentation), identified in BGM163 only [38].…”
Section: Other Classes Of Volatile Compoundsmentioning
confidence: 99%